2020
DOI: 10.7759/cureus.8888
|View full text |Cite
|
Sign up to set email alerts
|

Is COVID-19 Similar in Pregnant and Non-Pregnant Women?

Abstract: Approximately one-third of infected pregnant women died from severe acute respiratory syndrome coronavirus (SARS-CoV) and the Middle East respiratory syndrome coronavirus (MERS-CoV) epidemics of the past two decades. It is logical to predict that pregnant women infected with the novel coronavirus (SARS-CoV-2) might be at higher risk for severe illness, morbidity, or mortality compared with non-pregnant women. However, a review of the literature indicates that pregnant women are not more likely to be seriously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 22 publications
0
26
2
3
Order By: Relevance
“…In their literature review, Selim et al 17 report very small absolute risks of SARS‐CoV‐2 infection in pregnancy. Also, there is no evidence to date that pregnant women are more susceptible to SARS‐CoV‐2 infection than non‐pregnant women 17 . In general, the unique immunologic changes of pregnancy are thought to suppress the virulence of the virus 17 …”
Section: Pregnancy and Susceptibility Towards Sars‐cov‐2 Infection Comentioning
confidence: 99%
See 2 more Smart Citations
“…In their literature review, Selim et al 17 report very small absolute risks of SARS‐CoV‐2 infection in pregnancy. Also, there is no evidence to date that pregnant women are more susceptible to SARS‐CoV‐2 infection than non‐pregnant women 17 . In general, the unique immunologic changes of pregnancy are thought to suppress the virulence of the virus 17 …”
Section: Pregnancy and Susceptibility Towards Sars‐cov‐2 Infection Comentioning
confidence: 99%
“…hypoxia, pneumonia, etc. ), enhanced angiotensin‐converting enzyme 2 (ACE‐2) expression is thought to be linked to severity of symptoms 17 . A recent meta‐analysis reported that less than 20% of pregnant women need admission to the intensive care unit (ICU) 20 …”
Section: Pregnancy and Susceptibility Towards Sars‐cov‐2 Infection Comentioning
confidence: 99%
See 1 more Smart Citation
“…With this modified DT, our results had revealed a high prevalence (60%) of distress among COVID-19 patients. Being a novel global illness, no one is immune [12][13][14], several aspects of this disease are still vague in the eye of the general population, affecting many body organs and systems [15,16], and still has no definitive therapy, COVID-19 represents a real stressful condition and explains the high prevalence of distress among our cohort.…”
Section: Characteristicmentioning
confidence: 99%
“…The COVID-19 pandemic has generated concerns about its impact on pregnancy and child health outcomes. Whilst some studies have suggested that there is no difference in the risk of COVID-19 among pregnant women and the general population [15,16], others have shown that pregnancy increases the risk of contracting COVID-19 [17,18]. The risk of COVID-19 increases in pregnancy due to the weakened immune system associated with pregnancy [17].…”
Section: Introductionmentioning
confidence: 99%